Consideration of H2 generation in fluid governing equations of SPACE code. (September 2019) - Ha, Kwi Seok; Lee, Seung Wook; Kim, Kyung Doo
Abstract: The metal water reaction between the fuel clad and the coolant has been deemed important to safety analyses for transients for several decades. A Loss-of-coolant accident would cause the overheating of fuel clad which might involve a vigorously exothermic chemical reaction. The zirconium is widely used as a clad material and the element reacts remarkably with steam at high temperature of above 1000 K. The results of this reaction are the heat generation of level of fuel decay power, oxidized metal, and hydrogen generation. The system transient analysis code SPACE (Safety and Performance Analysis Code) which has been developed at the Korea nuclear industry has the correlation set modeling the metal-water oxidation, but the hydrogen generated by the reaction is not considered in the governing equations of the code. The governing equations were modified to model the hydrogen influx and steam extinction due to the reaction. The verification calculations for the code modification were performed using two conceptual problems. First, the modification of governing equations about the steam extinction corresponding to an inflow of hydrogen gas was reviewed by the forced hydrogen injection without a fuel model. Second, the hydrogen generation and temperature excursion due to the reaction were examined by the simulation of fuel without a nuclear heat source to investigate the validity of the redistribution of the reaction heat. Finally, the hypothetical accident of LBLOCA (Large break loss-of-coolant-accident) for the APR-1400 and the LOFT L2-5 test were calculated for a comparison with the calculation results by the original and modified codes.